2010
DOI: 10.1108/00251741011022563
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge creation and business format franchising

Abstract: PurposeThis article aims to contribute to the study of knowledge creation and management in business format franchising by focusing on the question of how franchisors can convert the tacit knowledge held by franchisees (such as insights, ideas, and hunches) to explicit knowledge.Design/methodology/approachThe article is conceptual and is largely anchored on the assumptions of the knowledge management, theories of organisational learning and organisational knowledge creation theory.FindingsThe findings emphasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 25 publications
1
52
0
10
Order By: Relevance
“…Dentre as diversas formas para a internacionalização, a franquia tem se destacado como uma das maiores forças propulsoras no processo de globalização das empresas de serviços (Pedro, Filipe, Reis, 2008), surgindo como uma alternativa estratégica para a internacionalização dessas organizações (Preble, 1992). Uma franquia pode ser caracterizada por um contrato que estipula as obrigações de duas partes (o franqueador e o franqueado) (Pfister et al, 2006;Sundbo et al, 2001) em que uma (a franqueadora) concede à outra (a franqueada) o direito de utilizar o seu nome, a sua marca, produzir os seus bens e/ou serviços; em troca do pagamento de uma taxa (Connel, 1997;Lindblom;Tikkanen, 2010;Pfister et al, 2006;Tikoo, 2005).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Dentre as diversas formas para a internacionalização, a franquia tem se destacado como uma das maiores forças propulsoras no processo de globalização das empresas de serviços (Pedro, Filipe, Reis, 2008), surgindo como uma alternativa estratégica para a internacionalização dessas organizações (Preble, 1992). Uma franquia pode ser caracterizada por um contrato que estipula as obrigações de duas partes (o franqueador e o franqueado) (Pfister et al, 2006;Sundbo et al, 2001) em que uma (a franqueadora) concede à outra (a franqueada) o direito de utilizar o seu nome, a sua marca, produzir os seus bens e/ou serviços; em troca do pagamento de uma taxa (Connel, 1997;Lindblom;Tikkanen, 2010;Pfister et al, 2006;Tikoo, 2005).…”
Section: Introductionunclassified
“…Dessa forma, em função do crescimento desse setor, a franquia tem se tornado uma estratégia popular (Lindblom & Tikkanen, 2010) e amplamente reconhecida pelas empresas como uma excelente oportunidade para a expansão de seus mercados (Doherty, 2007).…”
Section: Introductionunclassified
“…Studies explored the development of knowledge within the franchise network and migration of that knowledge throughout the network both among the franchisees and between a franchisee and franchisor (Darr, Argote, & Epple, 1995;Hoy, 2008;Kalnin & Mayer, 2004;Knot & McKelvey, 1999;Lindblom & Tikkanen, 2010;Sorenson & Sorensen, 2001;Watson et al, 2005). These studies showed how information originates and flows throughout the network; however, the perception of a presence of the dimension of a learning organization across the franchise network is underexplored.…”
Section: Notementioning
confidence: 99%
“…For example, the study by Szulanski (1996) found that most of the difficulties that have been found in transferring largely tacit knowledge are a result of the recipient's lack of experience to make effective use of new ideas, and due to the arduous relationships (according to him that is laborious and distant) between the source and the recipient. In a cross-border franchising context, the franchisors need to transfer both explicit knowledge, such as product and pricing information and also tacit knowledge, for example about new products and process development, to enable their franchisees to operate their units successfully (Gorovaia and Windsperger, 2013;Griessmair et al, 2014;Lindblom and Tikkanen, 2010;Watson et al, 2005). These knowledge characteristics then affect the process and success of the knowledge transfer in the cross-borders franchise networks.…”
Section: Networkmentioning
confidence: 99%
“…Knowledge is considered to be an important resource for franchisors, as franchisors develop competitive advantage on the basis of a unique business concept (Gorovaia and Windsperger, 2013;Lindblom and Tikkanen, 2010;Paswan and Wittmann, 2009;Wu, 2015). For example, Paswan and Wittmann (2009) have noted that a franchisee's success depends on their ability to leverage the knowledge of their franchisors.…”
Section: Conceptual Background Knowledge Transfer In Cross-border Framentioning
confidence: 99%